Adopsi Teknologi Blockchain untuk Meningkatkan Pelaporan Keuangan: Tinjauan Literatur - Zahara, Inna (Universitas Muhammadiyah Metro, 2024)
The rapid development of technology, particularly through the adoption of blockchain, has had a significant impact on the field of accounting. Blockchain, as a peer-to-peer (P2P) distributed network, opens new opportunities and presents challenges for the accounting profession. This article discusses the potential changes in accounting resulting from the adoption of blockchain technology. By utilizing blockchain, financial reporting can become more timely, transparent, and efficient, with the potential to reduce agency costs, capital costs, and enhance corporate value. While blockchain technology offers various advantages, including improved information quality, the adoption process is not without obstacles. Challenges such as standardization, scalability, and privacy issues need to be addressed to ensure successful integration and widespread adoption in financial accounting. The article notes that while blockchain technology can provide long-term benefits, the time and effort required to overcome technical and regulatory hurdles should be considered. Thus, the adoption of blockchain in accounting is seen as a promising step to enhance the quality of financial reporting, but it should be recognized that this journey requires commitment and the resolution of challenges encountered along the way